BRAND SWITCHING BEHAVIOR FROM SAMSUNG TO OPPO AMONG MILLENIALS - Dikdik Harjadi; Sifa Nurfatimah (Faculty of Economics and Business, University of Pasundan, 2021)
Along with the proliferation of smartphone manufacturers, the latest innovations and fascinating features are presented, such as selfie cameras, VOOC flash charge (the best fast charging) on their products, providing that selfie cameras accommodate people who love to upload their photos to social media. Nowadays, consumers’ needs have called attention to a lifestyle that requires them to make choices on goods or services that are compatible with their needs. This study employed a survey method, with samples comprising millennials in Kuningan Regency with a total of 283 respondents, in which the data collection was done using questionnaires, validity and reliability tests were conducted. Multiple linear regression was used in data analysis. The results showed that product features, lifestyle, and price had a positive and significant effect simultaneously and partially on brand switching decisions. However, price had a greater influence on consumers’ decisions to switch brands.